2002
DOI: 10.1080/028443102320791824
|View full text |Cite
|
Sign up to set email alerts
|

Sitting Pressure and Perfusion of Buttock Skin in Paraplegic and Tetraplegic Patients, and in Healthy Subjects: A Comparative Study

Abstract: The distribution of sitting pressure and ability to respond with reactive hyperaemia were studied in a group of paraplegic and tetraplegic patients (n = 8) with spinal cord lesions and healthy controls (n = 10) using a pressure sensitive plate and laser Doppler perfusion imager. The results show that the mean sitting pressure of the patients was 9.9 N/cm2 (left) and 11.7 N/cm2 (right) compared with 3.5 N/cm2 (left) and 3.6 N/cm2 (right) in controls. The differences were significant on both the left (p < 0.01) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
33
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 8 publications
6
33
1
Order By: Relevance
“…This again corresponds to the findings of Aissaoui et al [1], who reported SCI subjects as having a maximum pressure of 199-212 mmHg, equivalent to 271-288 g/cm 2 , in a standard chair with a flat-foam cushion. The pressure on the hard surface of 1,205 g/cm 2 , equivalent to 886 mmHg, also correlates with results from Thorfinn et al [16], who reported a maximum pressure of 11.7 N/cm 2 , equivalent to 877 mmHg or 1,192 g/cm 2 , in SCI subjects sitting on a glass plate.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This again corresponds to the findings of Aissaoui et al [1], who reported SCI subjects as having a maximum pressure of 199-212 mmHg, equivalent to 271-288 g/cm 2 , in a standard chair with a flat-foam cushion. The pressure on the hard surface of 1,205 g/cm 2 , equivalent to 886 mmHg, also correlates with results from Thorfinn et al [16], who reported a maximum pressure of 11.7 N/cm 2 , equivalent to 877 mmHg or 1,192 g/cm 2 , in SCI subjects sitting on a glass plate.…”
Section: Discussionsupporting
confidence: 77%
“…Other studies have compared and determined higher seating pressures in persons with SCI than in able-bodied subjects [16]. A recent study has derived an algorithm to define the area of highest pressure under the ischial tuberosity (IT) region and have shown that the IT weight-bearing area in subjects with SCI is half that of able-bodied controls [1].…”
mentioning
confidence: 99%
“…In most animal and human studies, longer occlusion times have been found to result in responses that are larger in magnitude. However, it has also been suggested that the hyperaemic response reaches a maximum with 5 minutes of occlusion (Faizi et al, 2009;Thorfinn et al, 2002;Thorfinn et al, 2007;Yvonne-Tee et al, 2008). For clinical assessment of vascular function, it has been suggested that 3 minutes (with LDF) or 5 minutes (with plethysmography) is the optimal occlusion duration, as those seem to result in maximal hyperaemic responses (Faizi et al, 2009;Yvonne-Tee et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that 50-80% of persons with SCI will, at some time after their injury, develop a pressure ulcer. [1][2][3][4][5] Pressure ulcers may interfere with mobility and community reintegration, can lead to a loss of independence, more serious medical complications, and result in profound economic and psychosocial consequences that may negatively impact quality of life. 1,6 Pressure ulcers most commonly occur at the ischial tuberosities (IT) due to the pressures associated with sitting, followed by the sacrum, in those with chronic SCI.…”
Section: Introductionmentioning
confidence: 99%
“…1,6 Pressure ulcers most commonly occur at the ischial tuberosities (IT) due to the pressures associated with sitting, followed by the sacrum, in those with chronic SCI. [1][2][3] A major focus of rehabilitation healthcare providers who serve this population is to educate the patient (and caregivers) to prevent the development of pressure ulcers. This includes education regarding etiology, risk factors, and proper positioning; prescribing appropriate equipment including pressure relieving cushions; and performance of timely and effective weight shifting.…”
Section: Introductionmentioning
confidence: 99%